The impact of safety culture towards safety performance with mediator of ISO9001 and OSH Administration - Ali Memon, Danish (2020)
Manufacturing industries plays a significant role in the Gross Domestic Product (GDP) of the country. However, great number of accidents occur due to the lack of safety culture implementation in the manufacturing industries. Accidents at workplace are uncontrollable but preventable. It was reported by Malaysia Department of Occupational Safety and Health that that from 2012 to 2016, 25% of death accidents, 75% of permanent disability accidents, and 64% of non-permanent disability accidents occurring in all sectors of the country occurred in manufacturing industry alone. Therefore, it is necessary to develop a framework to reduce health and safety risks in Johor manufacturing industries as to create safe and healthy environment for the employees. Subsequently, safety performance (SP) and safety culture (SC) are the essential parameters for the development of safe environment within the manufacturing industries. Therefore, this study aims to examine ISO9001 and occupational safety and health administration as a mediator between safety culture (SC) and safety performance (SP) in manufacturing industries in Johor, Malaysia. This study used Statistical Package for Social Science i.e. SPSS for demographic analysis, data screening and exploratory factor analysis whereas Structural Equation Modelling (SEM) with Partial Least Square (PLS) Version 3.0 was used to evaluate the measurement and structural relationship. Data was collected through questionnaires, distributed to senior managers, safety managers, safety operators and safety subordinators. Total 412 questionnaires were distributed and 255 were received. It was found that SC has positive and significant effect on SP inline with ISO and OSHA. It was statistically observed that OSHA has strong mediating effect between SC and SP. In contrast ISO9001 has weak mediator effect between SC and SP. Hence, it was found through PLS that SC and SP have satisfactory influence on OSHA with t-value 3.386. Therefore, this research can positively be beneficial and act as a guide for the Johor manufacturing industries to enhance the safety performance through safety culture implementation.